Identity Conflict in “The Cairo Trilogy” by Naguib Mahfouz: A Postcolonial Approach - Jefriadi, Jefriadi; Rahmah, Puja; Ummayah, Zakiyyah; Azmi, Hanif (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2025)
This study analyzes identity conflicts in modern Arabic literature through a postcolonial approach, focusing on “The Cairo Trilogy” by Naguib Mahfouz. By combining literary analysis with a sociopolitical examination of early 20th-century Egypt, this research aims to explore how social, political, and economic changes triggered by colonialism and the rise of nationalism shape the characters' identities in the novel. Additionally, this study highlights how Mahfouz portrays the tension between traditional values and modernity within the context of Egypt’s postcolonial transformation. Through a narrative ich in family and societal dynamics, “The Cairo Trilogy” not only illustrates Egypt’s social shifts but also reflects the complexity of individual identity formation in an ever-changing world. The identity conflicts experienced by the members of the Abdel Gawad family, particularly in confronting deepening modernization, serve as a microcosm of the internal and external struggles faced by Egyptian society during this transitional period. Beyond being a mere depiction of socio-political realities, the novel also offers a sharp critique of modernization and postcolonial cultural transformations that redefine societal values and ways of life. Thus, this work is not only significant as a literary masterpiece but also as a lens for understanding the evolving dynamics of identity in a postcolonial context